Hardness and microstructural variation of Al–Mg–Mn–Sc–Zr alloy. (March 2016) - Ikeshita, Sumiha; Strodahs, Ansis; Saghi, Zineb; Yamada, Kazuhiro; Burdet, Pierre; Hata, Satoshi; Ikeda, Ken-ichi; Midgley, Paul A.; Kaneko, Kenji
Highlights: Vickers hardness and microstructures of intragranular particles in Al–Mg–Mn–Sc–Zr alloy were examined as a function of the ageing period. Vickers hardness was increased by formation of block-shaped Al3 Sc precipitates growing along <1 0 0>Al with 1 0 0 and 1 1 0 of the precipitates. Microstructural characterizations confirmed the formation and growth of block-shaped Al3 Sc precipitates associated with ageing period. Abstract: Variations of Vickers hardness were observed in Al–Mg–Mn alloy and Al–Mg–Mn–Sc–Zr alloy at different ageing times, ranging from a peak value of 81.2 HV at 54 ks down to 67.4 HV at 360 ks, below the initial hardness value, 71.8 HV at 0 ks for the case of Al–Mg–Mn–Sc–Zr alloy. Microstructures of samples at each ageing stage were examined carefully by transmission electron microscopes (TEMs) both in two-dimensions and three-dimensions. The presence of different types, densities, and sizes of particles were observed dispersed spherical Al3 Sc1− x Zr x and also block-shaped Al3 Sc precipitates growing along <1 0 0>Al with facets 1 0 0 and 1 1 0 of the precipitates. TEM analysis both in two-dimensions and three-dimensions, performed on various samples, confirmed the direct correlation between the hardness and the density of Al3 Sc.